COPD Patients Had a Greater Probability of Getting GERD than the General Population. A Multi Center Study - Muhammad Asif Khan, Anwar Ul Haq, Imran Qadir Khattak, Farhan Zeb, Hameed Ullah, Muhammad Awais, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: COPD, a kind of obstructive lung disease, is characterized by partially reversible airflow limitation as a symptom. Emphysema and chronic bronchitis are two separate histological and clinical manifestations of chronic obstructive lung disease (COPD). Both components strongly emphasize individualism. The finding of an elevated incidence of gastro esophageal reflux disease (GERD) in this patient group may assist in the decision of whether or not to routinely assess COPD patients for the potential of GERD and treat it successfully. Objective: Understanding the prevalence of GERD among people who have the illness is crucial since it is linked to a poorer outcome in COPD patients. Methodology: Pulmonology department of HMC Hospital Peshawar conducted this multi center study. Analyzed data January 2019–January 2020. This experiment included 54 participants. Patients had complete physicals and histories (aged 21 to 80). After meeting inclusion and exclusion criteria, spirometer and the Q-questionnaire were administered. The same CPSP-certified technician collected all patients' spirometer readings, and the same CPSP-fellow specialist in pulmonology rated each patient's FEV1 following bronchodilator treatment using GOLD criteria (from "01" to "04"). As a percentage of COPD cases, Q-questionnaire respondents had GERD. Results: The mean age of the people was 57.36+08.35, with a standard deviation of 11.590. Men made up only 39% of the total patients, while women accounted for 61% of them. In those with COPD, GERD was present 51% of the time. Conclusion: According to the findings of this investigation, GERD occurred in individuals with COPD 51% more often than the general population. Keywords: COPD , GERD, Population